Konsep Poligami Dalam Hukum Islam - HARIYANTI (Jurnal Risalah Hukum, 2008)
Polygamy Marriage Practice actually does not have origin from Islam Law but earlierreligious civilizations in old age already adopt such practice. When Islam comes, thewidely accepted polygamy without doubt suddenly enters a regulation process. Thearrival of Islam Law brings along a strong base to regulate and to limit the negativeimpact resulted from polygamy (married with two women or more). Islam givesopportunity of polygamy to become a guidance of life. However, Islam put forth therequirements of polygamy, including the limit of four-wives-only, the capability ofbeing fair and equal, and taking the widow into account as way of charity.Key words: poligami (polygamy), perkawinan (marriage), adil (fair), suami (husband), istri (wife),lebih dari satu istri (married with two women or more).